An electrochemical device to control sample pH locally in Lab-on-PCB devices: An investigation into spatial resolution - Maxted, Grace; Estrela, Pedro; Moschou, Despina (Frontiers in Lab on a Chip Technologies, 2022)
During the recent pandemic outbreak, Lab-on-Chip devices did not manage to exploit their potential in rapid diagnosis of pathogens fully, mainly due to the lack of integrated sample preparation modules. This paper presents such a critical step, aiming to translate electrochemical pH control into practical protein preconcentration modules, easy to integrate with subsequent quantification modules seamlessly via Lab-on-PCB technology. In this work we present a device capable of electrochemically controlling the pH of a solution local to an individually addressed electrode in a PCB array. The electrodes were functionalised with an electropolymerised self-assembled monolayer of 4-Aminothiophenol and were subjected to voltages of 0.2-0.4 V, evaluating for the first time the bias effect both over time and over space. This study enables for the first time the implementation of this technique for electrochemical pH control into practical Lab-on-PCB devices such as isoelectric focusing, via the informed design of such electrode arrays of appropriate size and spacing.